2011
DOI: 10.1016/j.jvb.2011.03.016
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative IT offshoring relationships and professional role identities: Reflections from a field study

Abstract: While IT offshoring has generated heated debates both in scholarly circles and in the popular press, its impact on professional role identities and career experiences of situated individuals in both onshore and offshore locations has received much less attention. In this paper, we present a qualitative case study featuring a large global German technology firm and examine the multiple ways in which working within a collaborative offshoring arrangement has influenced the reconfiguration of German and Indian res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
1
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(48 citation statements)
references
References 22 publications
0
44
1
3
Order By: Relevance
“…According to our informants, central to these fears and biases were stereotypical notions about the inherent backwardness and inexperience of Indian organizations (see Beulen & Ribbers, 2003;Zaidman & Brock, 2009) and somewhat paradoxically, the threat of losing jobs to a talented Indian workforce in today's globally interconnected business environments (see Cohen & El-Sawad, 2007;Zimmermann & Ravishankar, 2011).…”
Section: Hybrid Practices and Power Asymmetriesmentioning
confidence: 99%
See 1 more Smart Citation
“…According to our informants, central to these fears and biases were stereotypical notions about the inherent backwardness and inexperience of Indian organizations (see Beulen & Ribbers, 2003;Zaidman & Brock, 2009) and somewhat paradoxically, the threat of losing jobs to a talented Indian workforce in today's globally interconnected business environments (see Cohen & El-Sawad, 2007;Zimmermann & Ravishankar, 2011).…”
Section: Hybrid Practices and Power Asymmetriesmentioning
confidence: 99%
“…In related academic disciplines such as organization studies, psychology, international business and industrial relations, recent research on offshore work has suggested that asymmetries of power grounded in history introduce a certain precariousness and anxiety into such relationships (Cohen & El-Sawad, 2007;Frenkel, 2008;Zimmermann & Ravishankar, 2011). The resulting fragility inevitably raises questions about how vendor organizations operating in highly globalized contexts and relying almost entirely on Western client organizations for business go about experiencing and negotiating historically embedded relations of power (see D 'Mello, 2005;Cohen & El-Sawad, 2007;Frenkel, 2008;Mir & Mir, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, they refused to move tasks to offshore locations, or they limited their effort in transferring the required knowledge (Zimmermann et al 2012;Zimmermann and Ravishankar 2014). Similarly, the fear of losing tasks and jobs has been identified as a reason for onshore members to withhold tasks and effort (Zimmermann and Ravishankar 2011;, to unduly criticize their offshore counterparts' work, and to avoid interacting with them as much as possible (Cohen and El Sawad 2007;Metiu 2006). Such fears can also cause onshore members to exclude offshore members from what they regard as their own, higher status onshore group, and to sabotage the offshore unit's chances of performing advanced tasks (Metiu 2006).…”
Section: Motivational Drivers Of Advanced Task Offshoringmentioning
confidence: 99%
“…OFD are evidently at play in IT offshoring relationships that appear to fail and collapse even when there are formal processes and detailed and unambiguous contracts (see Jain et al, 2011). In many cases, although they don't breakdown completely, IT offshoring relationships appear to frequently encounter uncertainty, tension and bitterness (see Ravishankar, et al, 2010;Zimmermann and Ravishankar, 2011) as a consequence of framing differences. The onus, therefore, is clearly on offshore and onshore members of the organization to manage the framing differences so that the OFD are reconciled and realigned.…”
Section: Frame Disputesmentioning
confidence: 99%
“…Put differently, 'cultural differences' are not merely a particular manifestation of cognitively constraining Secondly, notions about culture are frequently deployed to serve larger political agendas of special interest groups (Frenkel, 2008). For example, to protect onshore jobs that could otherwise be profitably moved offshore, managers can introduce exaggerated ideas about the cultural idiosyncrasies of offshore members (Zimmermann & Ravishankar, 2011).…”
Section: Culture As a Resource And Frame Disputesmentioning
confidence: 99%